An Observational Study of the School Health and Nutrition Programme in State Schools in Lusaka District, Zambia - Mulenga Napanje; Lisanne Du Plessis; Maritha Marais (Shiraz University of Medical Sciences, 2022)
Background: School health and nutrition programmes improve the health and nutritional status of learners, yet their implementation status in Zambia remains unknown. This study aimed to explore the implementation of school health and nutrition programme in one of the districts in Zambia.Methods: This was a descriptive, cross-sectional study conducted in Lusaka district, in 2015. The participating schools, including only state schools in Lusaka district were selected using stratified sampling method. Community and privately owned schools were not included. Herein, 40 school health and nutrition programme coordinators completed a questionnaire based on the guidelines provided by the Ministry of Education. Quantitative data were analysed via Microsoft Excel and Stata. The data obtained from open-ended questions were subjected to content analysis with prominent themes generated.Results: A School health and nutrition programme was observed in 42.5% (n=17) of the schools, but with no significant differences (P=0.601) between the urban and peri-urban ones. Due to insufficient funds and lack of supervision, only some of the recommended activities were implemented, such as school gardens, deworming, vitamin A and iron supplementation, and health education. The schools implementing school health and nutrition activities noted positive changes such as improvement in school attendance, pass rate, and a reduction in diarrhoea and bilharzia among their learners.Conclusion: School health and nutrition programme was implemented by less than half of the schools, still only partially. The effective implementation of the school health and nutrition programme is crucial to improve the health and nutritional status of learners. This necessitates that the Ministry of Education consistently follow up on school health and nutrition implementation.